OPTIMIZATION OF WIFI NETWORK IN KUALANAMU INTERNATIONAL AIRPORT - Hendra Harnanda; Andysah Putra Utama Siahaan; Leni Marlina; Muhammad Iqbal; Zulham Sitorus (PT. Radja Intercontinental Publishing, 2024)
A reliable and efficient WiFi network is a crucial facility to support the activities of passengers and visitors at Kualanamu International Airport. This study aims to identify issues affecting WiFi network performance and provide optimization solutions based on technical analysis and user needs. Data collection was conducted by measuring network parameters such as throughput, delay, jitter, and packet loss across various strategic airport areas, including waiting rooms, departure terminals, and commercial zones. The analysis revealed key challenges, such as high user density during peak hours and uneven access point distribution. To address these issues, the study proposes optimization steps, including bandwidth capacity expansion, reconfiguration of network devices, and the adoption of advanced technologies like WiFi 6. Implementing these recommendations is expected to enhance the quality of the WiFi network at Kualanamu International Airport, improve user experience, and support overall airport operations effectively.